Bamboo shoot resources of the Philippines I. Edible bamboo and the current status of the local bamboo shoot industry (2010)
This is the first comprehensive report on bamboo resources in the Philippines as edible bamboo shoots. Twenty-six provinces were visited along the creeks and rivers, bamboo plantations and the market places to determine the predominant bamboo species and the species with quality shoots. The current status of the local bamboo shoot industry was described as well as the regional preferences, processing, storage and bamboo shoot recipes noted. The study used primary data gathered through personal interviews, designed questionnaires and actual field surveys. The common species found in the area are all used as vegetable shoots. These were Bambusa blumena J.A. & J.H. Schultes, Bambusa vulgaris var vulgaris Schrader ex Wendland, Gigantochloa levis (Blnaco) Merr., Gigantochloa after (Hassk.) Kurz), Dendrocalamus asper (Schultes (f.) Backer ex Heyne, Bambusa merrilliana (Elmer) Rojo & Roxas and Bambusa philippinensis (Gamble) McClure. Bamboo shoots are called by many local names and the common names across the country are ‘labong’, ‘dabong’ ‘rabong’, ‘tambo’, ‘uvug’, etc. ‘Kawayang tinik’ or B. blumeana was the most predominant species in most regions and also the most popular edible species. ‘Kawayang kiling’ or Bambusa vulgaris was the second most common but only third in rank as edible species. The current status of bamboo shoot industry revealed that it is still at its infancy stage. The processing and marketing aspects of Bamboo shoot follow the traditional system. Significant observations during the study were discussed and the most alarming observation was the dwindling population of bamboo in natural stands especially along the major and minor rivers of the country. This is due to continuous illegal cuttings for poles and for bamboo shoot consumption and the non-planting of replenishment of this very important plant resource.